Delayed Perimesencephalic Subarachnoid Hemorrhage Probably Related to Remote Head Trauma: A Case Report - Ermir Roçi; Emili Mara; Gentian Vyshka (Clinical Case Reports)
ABSTRACT The diagnosis of a subarachnoid hemorrhage is challenging, and has important clinical, therapeutic and prognostic implications. Delayed NPMSAH (non‐aneurysmal perimesencephalic SAH) may involve subtle venous injury, aberrant venous anatomy or increased intracranial venous pressure. In all “idiopathic” cases, a remote traumatic event should be considered, and approached accordingly.